(untitled) - Franck, Irene M. (New York, 1988)
Explores the role throughout history of the occupations involved with science and technology, including alchemists, biologists, computer scientists, engineers, and physicists.
Keywords: Science,Technology,Khoa học,Công nghệ; History,History,Lịch sử,Lịch sử